THE IMPLEMENTATION OF MIND MAPPING TECHNIQUE IN TEACHING WRITING: A CASE STUDY AT MAN 13 JAKARTA - Edy Waloyo (IAIN Syekh Nurjati Cirebon, 2017)
Abstract: The objective of this study is to investigate the implementation of mind mapping in teaching writing narrative text. This study is conducted at the eleventh grade students of social class of Madrasah Aliyah Negeri 13 Jakarta. This study uses qualitative research design to find the answer of the objectives of the research. The data is collected by classroom observation, the teacher’s and the students’ interview, and students’ works. All the data are collected, classified, and analyzed. The data which could represent to answer the objective of the research are taken as the example. The example data are used as proves of the research finding. The research finding of this study shows that mind mapping has good influences to the students writing skill. It equips the students with clear guideline to write because it allows students think freely and creatively. The students understand the text organization of narrative, the tense in writing narrative, and how to determine the sequence of the story based on the mapping and key words provided. Key words: mind mapping, teaching writing, narrative text, qualitative